2018
DOI: 10.1038/s41416-018-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin suppresses hepatocellular carcinoma metastasis through CMKLR1-PTEN-Akt axis

Abstract: Our study has revealed the suppressive role and therapeutic potential of chemerin in HCC metastasis, providing both a prognostic marker and drug candidate for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
104
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(124 citation statements)
references
References 26 publications
(33 reference statements)
14
104
5
Order By: Relevance
“…These results are consistent with previous studies of augmented PTEN expression on the PI3k/Akt/mTOR pathway and its signaling constituents 25,27,28,33,35,55 .…”
Section: Chemerin Inhibits Pakt and Ps6 Signaling Leading To Decreasesupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous studies of augmented PTEN expression on the PI3k/Akt/mTOR pathway and its signaling constituents 25,27,28,33,35,55 .…”
Section: Chemerin Inhibits Pakt and Ps6 Signaling Leading To Decreasesupporting
confidence: 93%
“…Our group was the first to show that augmented chemerin in the TME -often downregulated in human tumors -resulted in recruitment of anti-tumor immune effector cells and significantly reduced tumor growth 23 . Several other groups have now shown similar findings both in preclinical and clinical scenarios 6,55,82 , supporting the robustness of these data. Our studies elucidate a novel axis between chemerin, CMKLR1, PTEN, and PD-L1 while simultaneously confirming chemerin's impact on PTEN/PI3k pathway expression 55 , extending this to additional tumor types (ie prostate, sarcoma).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…11 Down-regulated chemerin expression was detected in most tumor types, including melanoma and liver cancer, [11][12][13] and overexpression of chemerin could inhibit tumor growth and metastasis through different mechanisms including direct inhibition of the proliferation and migration of tumor cells or modulation of the tumor microenvironment. [12][13][14][15] For example, our previous study demonstrated that chemerin inhibits the progression of orthotopic murine liver cancer by reducing tumor-promoting inflammation, and others found that chemerin inhibits the invasion of human liver cancer cells. 13,14 Melanoma is a highly aggressive skin cancer, representing only 4% of skin cancers but accounting for 80% of deaths from dermatological cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] For example, our previous study demonstrated that chemerin inhibits the progression of orthotopic murine liver cancer by reducing tumor-promoting inflammation, and others found that chemerin inhibits the invasion of human liver cancer cells. 13,14 Melanoma is a highly aggressive skin cancer, representing only 4% of skin cancers but accounting for 80% of deaths from dermatological cancer. 16 Melanoma has been recognized as one of the most immunogenic malignancies with abundant infiltration of various immune cells.…”
Section: Introductionmentioning
confidence: 99%